'A new and more rigorous approach' to expert evidence in England and Wales?. (October 2015) - Ward, Tony
An amendment to the Criminal Practice Direction issued by the Lord Chief Justice of England and Wales lays down guidance for judges to follow in determining whether expert evidence is 'sufficiently reliable to be admitted'. Although the guidelines are based on those proposed by the Law Commission in 2011, they do not include a definition of 'sufficiently reliable', such as would have been provided by the Law Commission's Draft Bill, which the government declined to introduce. A criterion of 'sufficient reliability' must therefore be found within the common law. This article argues that 'sufficient reliability' is an aspect of 'helpfulness' and reflects the principle that experts should provide the jury with criteria with which to assess the weight of their evidence. Reliable evidence, in short, is evidence that provides the jury with sound reasons for relying on it. This criterion could be as rigorous as that proposed by the Law Commission, and possibly more so.